The exploration of future tendencies of the Lithuanian life insurance market - Belinskaja, Larisa (Ekonomika, 2009)
The objective of the research: The article treats the development tendencies of the Lithuanian life insurance market and evaluates its actual perspectives as compared to the markets of other European Union countries.The subjective of the research: The tendencies of the Lithuanian life insurance market development and its perspectives in the European context.Research methods: The analysis of the life insurance market embodies the arranged, systemized and carefully analyzed empirical data. The research uses the primal statistical data of the Lithuanian life assurance market collected and generalized by the Lithuanian Life Assurers Association and the Insurance Supervisory Commission of the Republic of Lithuania, and the statistical data of the Department of Statistics to the Government of the Republic of Lithuania concerning Lithuanian macroeconomics indexes. Some notices and assertions are circumstantial to the personal experience of the author.
Keywords: none